Development of Plan S monitoring and compliance tool in the context of PTCRIS for Portuguese National Science Foundation - Moreira, J. M.; Pardelha, F.; Laranjeira, C.; Pereira, F.; Novais, J.; Lopes, P.; Antunes, A.; Cardoso, E. (15th International Conference on Current Research Information Systems (CRIS2022), 2022)
The Portuguese Foundation for Science and Technology (FCT) has endorsed Plan-S since early 2021 and it is working towards implementing its obligations. To ensure an effective fulfillment of its open science policies, FCT is implementing a new monitoring and compliance tool, that will enforce the compliance with Plan-S as well as the new FCT’s open access (OA) policy. This paper details FCT’s approach to implement this tool and discusses the challenges of integrating information that is spread across multiple systems. The new tool will be built on top of infrastructures and services developed by FCT over the last years under the umbrella of the Portuguese Current Research Information System (PTCRIS) program. This tool comprises an operational component, integrated with the grant management system, and an analytical component, based on a Data Warehouse and Business Intelligence (DW/BI) system. The DW/BI system for the ecosystem of Science and Technology in Portugal will be developed using Kimball's Dimensional DW architecture, which advocates the incremental design and development of dimensional data marts linked by conforming dimensions. In this approach, data marts contain atomic and summarized data, corresponding to the development of elementary and derived dimensional models. Three data marts will be developed for the subject areas of funding, scientific results and for monitoring and compliance. The last data mart will calculate the compliance indicators for Plan- S as well as for FCT’s OA policy. The operational component of the new tool then receives, from the analytical component, the list of scientific results per funding registry along with data regarding compliance. A list of non-compliances for each scientific result will be the basis of a notification module that will inform the principal investigator (PI) and the FCT compliance officer.